Impact of Resistance Training on Physical Fitness Parameters: A Study of Body Composition and Energy Balance - Fatoni, Fatoni (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study aims to analyze the impact of resistance training on physical fitness parameters, especially on body composition and energy balance. The subjects in this study were students of the Department of Physical Education, Health and Recreation (PEHR), Universitas Negeri Makassar (UNM) who participated in a resistance training program for eight weeks, with a training frequency of three times per week. The method used was a quasi-experiment with a single group pretest-posttest design. Body composition measurements were carried out through analysis of body fat percentage, muscle mass, and body mass index (BMI), while energy balance was calculated based on estimates of daily energy intake and energy expenditure. The results showed a significant increase in muscle mass and a decrease in body fat percentage after resistance training intervention (p < 0.05). In addition, there was an improvement in energy balance, which was indicated by dietary adjustments and increased energy expenditure due to physical activity. These findings indicate that resistance training contributes positively to improving body composition and managing energy balance, which are important indicators of physical fitness. This study recommends the integration of resistance training into student fitness programs as a strategy to improve health and physical performance.